Implemetation of ROP In Stock Control to Minimize Losses Due to Expiry - Lukmanul Hakim Aziz; Richard Andre Sunarjo; Muhammad Ramdani; Qurotul Aini; Elisa Ananda Natalia; Lily Maria (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
Managing inventory with a limited shelf life is a crucial challenge in the supply chain, particularly in sectors where products are susceptible to rapid quality deterioration. Inaccuracies in ordering timing often lead to excess stock, which leads to financial losses due to product destruction, increased storage costs, and negative environmental impacts. This situation demands the implementation of more integrated and data-driven inventory control methods to optimize the procurement cycle sustainably. This study aims to analyze the effectiveness of implementing the Reorder Point (ROP) method integrated with historical demand and lead time data in minimizing the percentage of expired items. The main focus of the study is to establish ROP as a precise ordering timing mechanism, so that Safety Stock (SS) functions as an emergency buffer against uncertainty, rather than as excess inventory at risk of expiring. The research methodology includes analytical calculations of ROP, SS to mitigate demand and lead time variability, and Economic Order Quantity (EOQ) to determine the most economical order quantity. In addition, a literature review on the implementation of First Expired, First Out (FEFO) and First In, First Out (FIFO) systems is used as internal operational standards to ensure optimal stock rotation. The analysis results show that accurate ROP implementation is a key pillar in preventing expired goods. An optimal strategy requires synergy between prevention through precise ordering timing, internal control through strict stock rotation, and risk mitigation through proactive discount programs for products nearing expiration. The integration of ROP, SS, and EOQ has proven effective in reducing operational losses and supporting modern, efficient and sustainable inventory management practices.